Using Computer Technology under the Conditions of Modernization of Universities Educational Process - Oksana Chekan (Pedagogical Discourse, 2014)
In the article the scientific and methodological foundations for the use of computer technology by future teachers of preschool children in the modernization of the educational process of higher education is grounded. The experience of schools, indicating the possibility of using computer technology at all levels of the educational process is analyzed. The theoretical foundations of information education problems are studied. The key goal and objectives of means and methods of using computer -based technologies of the future teachers of preschool children in the modernization of the university educational process are determined. New requirements for future professionals in the field of early childhood education capacity building are offered. Didactic possibilities of the computer as a multifunctional training machine are proposed. The types of classes that use computer technologies are singled out. The method of multimedia technology in the classroom is demonstrated. The method of design lectures using computer -based technology in the modernization of the educational process in higher education is offered. Conclusions from the research  described  and recommendations for further research in this direction are grounded.